DAYA TERIMA KONSUMEN TERHADAP PRODUK STIK BIJI NANGKA BERBAGAI RASA - Kusti Indrianti; Karina Chika Wulandari; Nofalia Kholfatul Anggraeni; Kevin Jans Saito; Noer Sizeh; Irfany Rupiwardani (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Jackfruit seeds have high nutrient content such as carbohydrates and proteins, so they can be used as a potential food ingredient. One of the food product ingredients can be in the form of concrete seed sticks and among the product community in the form of sticks that are very popular with the community. The purpose of this research is to find out the consumer acceptance of stick products of concrete seeds in various flavors. The non-parametric statistical method uses the Friedman Test and the determination of the best treatment uses the index of effectiveness. The results showed that the best combination of treatments on consumer acceptance of organoleptic concrete seed sticks was obtained from spicy-flavored concrete seed sticks with a product value of 0.48 with the following characteristics: average panelist preference for taste 4.32; 2.52 color and 2,96 flavor.